Gaia Photometric Catalogue: the calibration of the DR2 photometry. Issue Volume 14:Issue A30(2018) (August 2018) - Evans, D. W.; Riello, M.; De Angeli, F.; Carrasco, J. M.; Montegriffo, P.; Fabricius, C.; Jordi, C.; Palaversa, L.; Diener, C.; Busso, G.; Cacciari, C.; Pancino, E.; et al.
Abstract: Gaia DR2 was released in April 2018 and contains a photometric catalogue of more than 1 billion sources. This release contains colour information in the form of integrated BP and RP photometry in addition to the latest G-band photometry. The level of uncertainty can be as good as 2 mmag with some residual systematics at the 10 mmag level. The addition of colour information greatly enhances the value of the photometric data for the scientific community. A high level overview of the photometric processing, with a focus on the improvements with respect to Gaia DR1, was given. The definition of the Gaia photometric system, a crucial part of the calibration of the photometry, was also explained. Finally, some of the photometric improvements expected for the next data release were described.